Análise da videoanimação Out of Sight à luz da semiótica social - Lima, Isabela Vieira (2022)
The objective of this dissertation is to analyze the semiotic modes and semiotic resources present in the video animation Out of Sight (2010) as well as their potential meanings in the social representation of Chico, a blind child. Deriving from multimodal configurations, the organization of video animations seeks to represent ways of seeing, feeling, and interpreting reality through the multimodal orchestration of different semiotic modes and semiotic resources such as lighting, look, color, music, and voice, among others. These texts present, in their constitution, the semiotic choices of the producers, which are organized in the form of references to guide the readers-spectators through the interpretative path. As a result, we chose the following question as a problem: what contributions can the theory of Social Semiotics bring to the analysis and understanding of social representations presented in video animations, based on the different semiotic modes and semiotic resources that constitute them? To discuss this issue, the theory of Social Semiotics is used (HODGE; KRESS, 1988), addressing the multimodal organization of texts, taking into consideration their conditions of production and reception as well as the different semiosis that are organized in the (re)construction of meanings. Thus, two types of research were developed: i) a theoretical research, in which the main theoretical assumptions linked to the theory of Social Semiotics are discussed. In addition, the theoretical body also has a historical overview about the origin and development of video-animations; ii) an applied research, from which the semiotic modes and resources in the video animation are listed and discussed, through a methodological table inspired by Gualberto and Pimenta (2019). Based on our research, we selected some findings, namely: a) Social Semiotics is a theory that contributes to the analysis of social representations that are presented by multimodal texts, such as video animation; b) representations can be re-signified from the innovative use of consolidated semiotic modes and resources; c) text producers build their project of saying from the multimodal orchestration of different modes and resources during the semiotic work; d) the Grammar of Visual Design, despite referring to static images, can be used for the analysis of texts in movement, as it has instruments that allow verifying the processes that appear between pictures, such as angle, framing, look, etc; e) Social Semiotics has an extensive framework of texts that rely on a multimodal approach to explore different semiosis produced by subjects during the communication/interaction process. Therefore, in addition to verifying the potential of semiotics in the constitution of multimodal texts such as video animations, we believe that this work may have contributed to the theories/methodologies of analysis of multimodal texts, being more widespread in the academic environment, notably in the area of linguistics, which is primarily concerned with the study of the uses of languages in different discursive situations. Added to this is the possibility of bringing incentives to theories/methodologies related to multimodal texts and their contributions to the analysis of social representations.